IMPLEMENTATION OF EDUCATIONAL PROGRAMS USING DISTANCE LEARNING TECHNOLOGIES - Nadezda V. Shestak; Natilia M. Podzolkova (Высшее образование в России)
The article is devoted to the implementation of distance learning technologies in the system of continuous professional education. The problem solution the authors see in the professional development of teachers in the field of distance learning technologies. The authors share the experience of the webinar organization in Russian Medical Academy of Postgraduate Education. There are viewed such forms of distant learning as webinars, service box, and SAAS services.